"THE ROLE OF POST-DIVERSION SUPERVISION IN PREVENTING RECIDIVISM AND SOCIAL REINTEGRATION OF CHILDREN" - Dian Ayu Raspati; Faizin Sulistio (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Diversion in the juvenile justice system aims to promote rehabilitation and avoid formal justice processes. However, weak post-diversion supervision increases recidivism and hinders social reintegration. This study identified regulatory challenges, limited resources, and a lack of inter-agency coordination in the post-diversion supervision of children. The roles of the Child Protection Agency (Bapas), families, and communities are crucial in ensuring successful rehabilitation. Policy reforms and strengthening of restorative justice-based monitoring systems are needed. More effective supervision will help children lead better lives and prevent re-offending.